Implementation of MBKM Program in the Civil Engineering Department, Faculty of Engineering, UNP - Dzaki, Muhammad Afi; Yustisia, Henny (Universitas Negeri Padang, 2024)
The implementation of the MBKM Program in the Civil Engineering Department at FT UNP was investigated to analyze its effectiveness and challenges. This descriptive qualitative study aimed to explore how the program is executed, the obstacles encountered by students, and the advantages it offers. Through interviews with six MBKM participant students and three department lecturers, data analysis revealed 17 codes, 10 sub-themes, and four main themes, including MBKM programs and activities, experiences and skills, administrative concerns, and challenges faced. The findings underscored the program's positive impact on students' skill enhancement, practical exposure, and holistic understanding of professional environments. Participation in activities such as PMM, Kampus Mengajar, and Magang Merdeka facilitated practical experiences, networking, and skill development, albeit challenges like administrative issues and credit conversion were identified. Overall, the MBKM Program significantly contributes to students' personal and professional growth, emphasizing the importance of effective coordination between stakeholders to optimize its implementation.